La responsabilidad social empresarial y su incidencia en los accidentes de trabajo en el sector minero en el Perú: 2008 - 2015 - Linares Chávez, Luis Eduardo (2017)
Peru has become one of the destination countries for mining investment in the world. The high international prices of metals and the generation of income for the country are leading the economy to revolve around this type of activities motivated by the extractive industries. However, mining industrial activities, generate occupational hazards such as accidents at work and occupational diseases of irreversible character; these damages constitute a reality of the state of unpredictability in the health and safety at work, since the harmful elements that emanate from the extraction of minerals, the underground cavities of the mines, complex operations of refinery of metals and mineral concentrating plants are generators of physical agents, mineral powders, chemical agents, radioactive agents, emanations of antimony and others. Faced with this reality, only with prevention can it be avoided or mitigated. The present research work "THE CORPORATE SOCIAL RESPONSIBILITY AND ITS INCIDENCE IN THE ACCIDENTS OF WORK IN THE MINING SECTOR IN PERU: 2008-2015" has as main objective To determine the incidence of Corporate Social Responsibility in the work accidents in the sector miner in Peru during 2008-2015. On the other hand, we will determine the number of work accidents that occurred in the mining sector in Peru during the study period, identify the causes that have affected the high rate of work accidents in mining companies in Peru, Social Entrepreneurship and its strategies in the mining sector. We will identify and analyze the trend of the reduction of work accidents in the mining sector. In order to be able to develop the present research work the descriptive method has been used and the technique that will apply in this research is the bibliographical research, on the other hand we have techniques for the Treatment and analysis of information that are: Documentary analysis, tabulation of tables with quantities and percentages, graphic formulation, bibliographic review; and the techniques for data processing that I will name below: Sorting and classification, computerized processing, using computer equipment, as a research design we have a box. As a possible response to the problem, the following hypothesis was formulated: Corporate Social Responsibility has had a significant impact on the reduction of occupational accidents in the mining sector in Peru during 2008-2015. Having developed the present research work and evaluated the results obtained, it was concluded that thanks to the Social Responsibility policies applied by the mining companies, the number of accidents within the mining companies was considerably reduced, being the main causes of the crashes, rockslides, poisoning victims and traffic accidents. Another characteristic is that the highest percentage of accidents (an average of 67% in the last six years), occurs among workers of mining contractors. The productivity of companies today is fundamental to their competitiveness in this era of globalization and work accidents represent a malfunction in common operations, A work accident in an organization implies an unnecessary cost generation and allows to analyze that some parts of the operational process of the organization are risky and reflect the errors in the internal system, which causes the need to know how they arose and thus rectify and / or prevent the part of the process that generated them, in order to promote the continuous improvement in the organization in the optimization of both economic and human resources.